judul skripsi: hubungan antara lingkungan belajar di sekolah dengan prestasi belajar matematika siswa kelas IV min 2 alor - siti inayah; Jusriadi; Patris L. Lengmani; Rizal P. Plaikari (STKIP Muhammadiyah Kalabahi, 2026)
Based on observations made by researchers on June 14, 2024, information was obtained from Mr. Sumanri Sabar as the homeroom teacher of class IV MIN 2 Alor that MIN 2 Alor uses the 2013 curriculum. What was obtained was about the learning problems obtained from 20 students who did not complete, including: lack of a supportive physical environment such as: a). learning facilities and infrastructure, learning resources, b). The social environment concerns the relationship between students and their friends and students with their teachers. c). The academic environment is the school atmosphere and the implementation of teaching and learning activities and various curricular activities. ?